Use of antiepileptic medications for seizures' prevention during subarachnoid hemorrhage: A retrospective observational study - Alghadeer, Sultan; Binhazza, Reham M.; Alwahibi, Abdulrahman; Alsaloom, Feda F.; Alshaya, Abdulrahman I.; Alyahya, Hayaa; Al-Ghamdi, Abrar; Alghamdi, Abdulrahman A. (Medicine (Baltimore), 2024)
The use of prophylactic antiepileptic drugs (AEDs) post-subarachnoid hemorrhage (SAH), particularly aneurysmal SAH, is controversial, with limited data available. This has led the new American Heart Association/American Stroke Association (AHA/ASA) guidelines to recommend against using AEDs. This study is aimed at determining whether the use of AEDs for primary prophylaxis is effective in reducing the incidence of seizures post-SAH. A retrospective observational study was conducted utilizing a reviewing chart for the period starting from June 2015 to the end of 2021. The reviews were conducted in the acute care areas of 2 tertiary hospitals primarily to assess the efficacy of AEDs against seizures in patients with SAH (particularly aneurysmal SAH). This was done by comparing the occurrence of early, late, and overall incidence of seizures between patients who received AEDs versus those who did not. Of the 62 patients, who mostly presented with aneurysmal SAH (71%), 42 received AEDs and 20 did not. Mostly, the baseline characteristics between the 2 groups were comparable. A few patients on AEDs developed early (n = 4/38), late (n = 3/29), and overall seizures (n = 6/33), whereas no early, late, or overall incidence of seizures was presented in the group who did not receive AEDs. However, this difference showed no significance (P > .05). The subjects who were given AEDs showed significantly longer hospital stays (42.11 ± 51.43 vs 14.10 ± 7.17; P = .002) and higher mortality rates (7/11 vs 0/11; P = .026). For all patients who received AEDs for prophylaxis, the overall incidence of seizures was negatively associated with the Glasgow coma scale (OR: 0.798; 95% CI 0.657-0.978; P = .022). Our findings support the 2023 AHA/ASA guideline recommendation to avoid using routine AEDs for prophylaxis for all SAH patients. Proper and careful stratification methods should be implemented in each given scenario.